Composite sodium vanadium phosphate material, preparation method thereof, positive pole piece and secondary battery
By using a segmented calcination method and controlling calcination parameters, the problems of high impurity content and low compaction density of sodium vanadium phosphate materials were solved, improving the electrochemical performance of composite sodium vanadium phosphate materials, making them suitable as cathode materials for sodium-ion batteries.
Patent Information
- Application Number
- CN202511659412.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-13
- Publication Date
- 2026-02-06
AI Technical Summary
In existing sodium vanadium phosphate preparation processes, sodium vanadium phosphate has a high impurity content and low compaction density, resulting in poor battery performance.
A segmented calcination method is adopted, in which an oxidation-reduction reaction is first carried out at a low temperature, followed by crystal growth and carbon coating at a high temperature. By controlling the material ratio and calcination parameters, impurities are avoided and the density and conductivity of the material are improved.
The electrochemical performance of the composite sodium vanadium phosphate material was significantly improved, including higher compaction density and conductivity, reduced powder internal resistance, and enhanced battery electrochemical performance.
Smart Images

Figure CN121470458A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of sodium-ion battery technology, specifically to a composite sodium vanadium phosphate material and its preparation method, a positive electrode sheet, and a secondary battery. Background Technology
[0002] Sodium vanadium phosphate (Na3V2(PO4)3) has advantages such as high theoretical specific capacity, high voltage platform, high energy density, long cycle life and high safety as a cathode material for batteries (such as those used in new energy vehicles), and has good application prospects in sodium-ion batteries.
[0003] Currently, the main preparation processes for sodium vanadium phosphate include the sol-gel method, solid-state method, and hydrothermal method. These methods all utilize high-valence vanadium sources and carbon sources for carbothermic reduction reactions to prepare composite sodium vanadium phosphate. During the carbothermic reduction reaction, over-reduction occurs, leading to the generation of magnetic substances. Simultaneously, it consumes additional carbon and generates large amounts of waste gases such as carbon dioxide and water vapor. These waste gases react with active amorphous carbon to produce strong reducing gases such as carbon monoxide and hydrogen, which can cause over-reduction of the vanadium and phosphorus sources, resulting in impurities and impurity phases. Understandably, the large amount of waste gas generated during the preparation process hinders particle growth, resulting in low compaction density of the prepared sodium vanadium phosphate. Furthermore, the large amount of waste gas also causes significant atmospheric fluctuations within the calcining furnace, leading to unstable carbon content on the surface of the sodium vanadium phosphate.
[0004] Therefore, there is an urgent need to propose a new method for preparing composite sodium vanadium phosphate materials to solve the technical problems of high impurity content and low compaction density of sodium vanadium phosphate prepared by existing processes. Summary of the Invention
[0005] In view of the technical problems existing in the background art, this application provides a composite sodium vanadium phosphate material and its preparation method, positive electrode sheet and secondary battery, aiming to solve the technical problems of high impurity content and low compaction density of sodium vanadium phosphate prepared by existing preparation processes.
[0006] In a first aspect, embodiments of this application provide a method for preparing a composite sodium vanadium phosphate material, comprising the following steps: mixing sodium metavanadate, sodium dihydrogen phosphate, phosphorous acid, and an inorganic carbon source and then dispersing the mixture to obtain a dispersed material; calcining the dispersed material in stages under an inert atmosphere to obtain the composite sodium vanadium phosphate material; wherein the staged calcination includes a first calcination and a second calcination, the calcination temperature of the first calcination being 120℃-200℃, and the calcination temperature of the second calcination being 600℃-650℃.
[0007] In the technical solution of this application embodiment, phosphorous acid with reducing properties, sodium metavanadate with oxidizing properties, sodium dihydrogen phosphate, and an inorganic carbon source are dry-mixed. First, at a lower first calcination temperature, phosphorous acid, sodium metavanadate, and sodium dihydrogen phosphate undergo a redox reaction, where vanadium is reduced to the trivalent state and phosphorus is oxidized to the pentavalent state. Because the first calcination temperature is low, the inorganic carbon source does not participate in the redox reaction, thereby reducing the generation of reducing gases and avoiding the generation of impurities. Subsequently, at a higher second calcination temperature, the sodium vanadium phosphate crystals further grow and fill the pores generated during the first calcination, making the particles more compact and the compaction density higher. At the same time, the inorganic carbon source coats the sodium vanadium phosphate, significantly improving the conductivity of the composite sodium vanadium phosphate material and reducing the powder internal resistance, thereby significantly improving the electrochemical performance of the composite sodium vanadium phosphate material.
[0008] In some embodiments, during the preparation of the dispersed material, the molar ratio of sodium metavanadate, sodium dihydrogen phosphate, phosphorous acid, and inorganic carbon source is 2:(1.02-1.05):2:(1-2); and / or, the dispersion treatment includes ball milling dispersion treatment, and the D100 particle size of the dispersed material is ≤1μm.
[0009] In this embodiment, by controlling the molar ratio of sodium metavanadate, sodium dihydrogen phosphate, phosphorous acid, and inorganic carbon source to 2:(1.02-1.05):2:(1-2), sodium metavanadate, sodium dihydrogen phosphate, and phosphorous acid can fully undergo redox reactions, avoiding the generation of impurities. At the same time, the added inorganic carbon source can form a carbon coating layer on the material surface, further improving the conductivity of the material and reducing the internal resistance of the powder. Furthermore, by controlling the D100 of the dispersed material to ≤1μm, the specific surface area of the particles in the dispersed material can be increased, facilitating complete reaction after the particles have sufficient contact, thereby improving the performance of the material.
[0010] In some embodiments, during the preparation of the dispersed material, the inorganic carbon source includes at least one of graphene, carbon nanotubes, carbon nanofibers, and conductive carbon black.
[0011] In this embodiment, by selecting an inorganic carbon source for coating, the conductivity is better than that of an organic carbon source. Furthermore, the inorganic carbon source is less likely to react with waste gases such as water vapor generated after the oxidation and reduction of sodium metavanadate, sodium dihydrogen phosphate, and phosphorous acid at the first calcination temperature, thereby resulting in a higher carbon content in the coating, which significantly improves the conductivity of the material and reduces the internal resistance of the powder. At the same time, the inorganic carbon source is widely available and easy to obtain, which is beneficial for large-scale industrial production.
[0012] In some embodiments, before the dispersed material is calcined in stages, the dispersed material is further subjected to demagnetization treatment, and the content of magnetic foreign matter in the dispersed material after demagnetization treatment is <1ppm.
[0013] In this embodiment, by controlling the content of magnetic foreign matter in the dispersed material to be <1ppm, the purity of the prepared composite sodium vanadium phosphate material can be increased, thereby reducing the impact of magnetic foreign matter impurities on the electrochemical performance of the composite sodium vanadium phosphate material.
[0014] In some embodiments, the first calcination includes a first heating section and a first holding section. The heating rate of the first heating section is 0.2℃ / min-0.5℃ / min, the temperature of the first holding calcination is 120℃-200℃, and the time is 1h-2h. The second calcination includes a second heating section and a second holding section. The heating rate of the second heating section is 4℃ / min-6℃ / min, the temperature of the second holding section is 600℃-650℃, and the time is 3h-4h.
[0015] In this embodiment, by controlling the heating rate of the first heating stage to 0.2℃ / min-0.5℃ / min, the particles in the dispersed material are allowed to come into full contact, which is beneficial for subsequent full reaction. The temperature of the first holding stage is controlled at 120-200℃ for 1-2 hours, allowing the phosphorous acid, sodium metavanadate, and sodium dihydrogen phosphate in the dispersed material to undergo redox reactions at a lower temperature, avoiding the generation of impurities. Furthermore, by controlling the heating rate of the second heating stage to 4℃ / min-6℃ / min, the temperature of the second holding stage can be quickly reached, improving preparation efficiency. By controlling the temperature of the second holding stage to 600℃-650℃ for 3-4 hours, calcination at high temperatures results in denser particles and higher compaction density in the prepared material. Simultaneously, under high-temperature conditions, the inorganic carbon source coats the sodium vanadium phosphate to form a carbon coating layer, which significantly improves the conductivity and reduces the internal resistance of the powder in the composite sodium vanadium phosphate material, thereby significantly improving the electrochemical performance of the composite sodium vanadium phosphate material.
[0016] In some embodiments, during the segmented calcination process, the volume ratio of the inert gas introduced into the first heating section, the first heat preservation section, the second heating section, and the second heat preservation section is (6-10):(4-6):(2-4):1; and / or, the inert gas includes at least one of nitrogen and argon.
[0017] In this embodiment, by controlling the volume ratio of the inert gas introduced into the calcination furnace in the first heating section, the first heat preservation section, the second heating section, and the second heat preservation section, the reaction can be fully carried out, and the electrochemical performance of the composite sodium vanadium phosphate material can be improved.
[0018] In some embodiments, the humidity of the calcining furnace in the first insulation section is ≤2.0%, and the furnace pressure is 30Pa-60Pa; and / or, the furnace pressure in the second insulation section is 30Pa-50Pa.
[0019] In this embodiment, by controlling the humidity of the calcining furnace in the first insulation section to be ≤2.0% and the furnace pressure to be 30Pa-60Pa, the water vapor generated by the oxidation-reduction reaction in the first insulation section can be prevented from reacting with the inorganic carbon source in the second insulation section, reducing the content of coated carbon and thus reducing the electrochemical performance of the composite sodium vanadium phosphate material; by controlling the furnace pressure of the second insulation section to be 30Pa-50Pa, it is beneficial to form a carbon coating layer on the material surface.
[0020] Secondly, embodiments of this application provide a composite sodium vanadium phosphate material, prepared by any of the above-mentioned preparation methods, wherein the compaction density of the composite sodium vanadium phosphate material is 2.2 g / mL-2.4 g / mL, and the specific surface area of the composite sodium vanadium phosphate material is 8 m². 2 / g-10m 2 / g, the D50 particle size of the composite sodium vanadium phosphate material is 1μm-3μm.
[0021] In the technical solution of this application embodiment, the prepared composite sodium vanadium phosphate material has a high compaction density.
[0022] Thirdly, embodiments of this application provide a positive electrode sheet comprising the aforementioned composite sodium vanadium phosphate material.
[0023] In this embodiment, the positive electrode contains the aforementioned composite sodium vanadium phosphate material, thus exhibiting good electrochemical performance.
[0024] In a fourth aspect, embodiments of this application provide a secondary battery, including the aforementioned positive electrode sheet.
[0025] In this embodiment, the secondary battery includes the aforementioned positive electrode sheet, and therefore has good electrochemical performance.
[0026] Beneficial effects: This application involves dry mixing of reducing phosphorous acid, oxidizing sodium metavanadate, sodium dihydrogen phosphate, and an inorganic carbon source. At a first calcination temperature, phosphorous acid, sodium metavanadate, and sodium dihydrogen phosphate undergo a redox reaction, reducing vanadium to its trivalent state and oxidizing phosphorus to its pentavalent state. Because the first calcination temperature is low, the inorganic carbon source does not participate in the redox reaction, thus reducing the generation of reducing gases and avoiding impurities. Subsequently, at a second calcination temperature, the sodium vanadium phosphate crystals further grow and fill the pores generated during the first calcination, resulting in denser particles and higher compaction density. Simultaneously, because carbon loss is controlled, the carbon coating layer formed by the inorganic carbon source coating the sodium vanadium phosphate effectively improves the conductivity of the composite sodium vanadium phosphate material and reduces the powder's internal resistance, thereby effectively improving the electrochemical performance of the prepared composite sodium vanadium phosphate material.
[0027] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0028] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0029] Figure 1 This is a SEM image of the composite sodium vanadium phosphate material prepared in Example 1 of this application; Figure 2 The image shows a SEM image of the composite sodium vanadium phosphate material prepared in Comparative Example 1 of this application. Figure 3 The image shows the XRD pattern of the composite sodium vanadium phosphate material prepared in Example 1 of this application. Figure 4 This is a charge-discharge curve of the secondary battery prepared using the composite sodium vanadium phosphate material obtained in Example 1 of this application. Detailed Implementation
[0030] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0032] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0033] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0034] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0035] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).
[0036] Currently, the main preparation processes for sodium vanadium phosphate materials include the sol-gel method, solid-state method, and hydrothermal method. However, the sodium vanadium phosphate materials prepared by these methods suffer from technical problems such as high impurity content and low compaction density.
[0037] To address the technical problems of high impurity content and low compaction density in existing sodium vanadium phosphate materials, this application provides a composite sodium vanadium phosphate material, its preparation method, a positive electrode sheet, and a secondary battery.
[0038] In a first aspect, this application provides a method for preparing a composite sodium vanadium phosphate material, comprising the following steps: mixing sodium metavanadate, sodium dihydrogen phosphate, phosphorous acid, and an inorganic carbon source and then dispersing the mixture to obtain a dispersed material; calcining the dispersed material in stages under an inert atmosphere to obtain the composite sodium vanadium phosphate material; wherein the staged calcination includes a first calcination and a second calcination, the calcination temperature of the first calcination being 120℃-200℃, and the calcination temperature of the second calcination being 600℃-650℃.
[0039] In this application, phosphorous acid (which has reducing properties), sodium metavanadate (which has oxidizing properties), sodium dihydrogen phosphate, and an inorganic carbon source are dry-mixed and then subjected to a redox reaction at a lower first calcination temperature. Vanadium is reduced to its trivalent state, and phosphorus is oxidized to its pentavalent state. The chemical equation for the reaction is as follows: 2NaVO3+NaH2PO4+2H3PO3→Na3V2(PO4)3+4H2O As can be seen from the above equations, the burn-off rate of the raw materials in this application is very low, around 14.2%, significantly lower than the burn-off rate of raw materials used in traditional carbothermic reduction reactions using high-valence vanadium and carbon sources (generally above 30%). Furthermore, due to the lower temperature of the first calcination, the inorganic carbon source does not participate in the redox reaction, thereby reducing the generation of reducing gases and avoiding impurities. Subsequently, at a higher second calcination temperature, the sodium vanadium phosphate crystals further grow and fill the pores generated during the first calcination, resulting in denser particles and higher compaction density. Meanwhile, the inorganic carbon source coats sodium vanadium phosphate, significantly improving the conductivity and reducing the internal resistance of the composite sodium vanadium phosphate material, thereby significantly improving the electrochemical performance of the composite sodium vanadium phosphate material. If the first calcination temperature is too low, the redox reaction will be incomplete, resulting in impurities. If the first calcination temperature is too high, some inorganic carbon source will undergo redox reaction, producing impurity phases. If the second calcination temperature is too low, the coating will be incomplete, reducing the electrochemical performance of the composite sodium vanadium phosphate material. If the second calcination temperature is too high, the particles will grow, further reducing the electrochemical performance of the material.
[0040] Specifically, the temperature of the first calcination can be 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, or any value within this range; wherein, the calcination temperature of the first calcination is preferably 120-170℃, more preferably 150-170℃. The temperature of the second calcination can be 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, or any value within this range.
[0041] Furthermore, in some embodiments, during the preparation of the dispersed material, the molar ratio of sodium metavanadate, sodium dihydrogen phosphate, phosphorous acid, and inorganic carbon source is 2:(1.02-1.05):2:(1-2); and / or, the dispersion treatment includes ball milling dispersion treatment, and the D100 particle size of the dispersed material is ≤1μm.
[0042] In this application, by controlling the molar ratio of sodium metavanadate, sodium dihydrogen phosphate, phosphorous acid, and inorganic carbon source to 2:(1.02-1.05):2:(1-2), the sodium metavanadate, sodium dihydrogen phosphate, and phosphorous acid can fully undergo redox reactions, avoiding the generation of impurities. Simultaneously, the inorganic carbon source can form a uniform carbon coating layer on the material surface, thereby improving the material's conductivity and reducing the powder's internal resistance. If the molar ratio of sodium metavanadate, sodium dihydrogen phosphate, phosphorous acid, and inorganic carbon source is too low, the reaction will be incomplete, resulting in impurities and incomplete carbon coating, thus reducing the material's electrochemical performance. If the molar ratio is too high, there will be an excess of raw materials, also generating impurities, and the excessive carbon content will cause some particles to agglomerate, further reducing the material's electrochemical performance.
[0043] Furthermore, in this application, by controlling the D100 particle size of the dispersed material to be ≤1μm, the specific surface area of the particles in the dispersed material can be increased, which facilitates the complete reaction after the particles come into full contact, thereby improving the performance of the material. If the D100 particle size of the dispersed material is large, the performance of the material will be reduced.
[0044] Specifically, the molar ratio of sodium metavanadate, sodium dihydrogen phosphate, phosphorous acid, and inorganic carbon source can be 2:1.02:2:1, 2:1.03:2:1.2, 2:1.04:2:1.4, 2:1.05:2:1.6, 2:1.05:2:1.8, 2:1.05:2:2, or any ratio within this range.
[0045] Understandably, the dispersion treatment can be selected from conventional dispersion methods in the prior art according to actual needs, as long as the material can be uniformly dispersed. For example, in this application, the dispersion treatment preferably includes ball milling dispersion treatment, which is carried out in a planetary ball mill. The inner wall of the planetary ball mill is made of ceramic material (zirconia ceramic with a yttrium content of 4%), the grinding balls are made of zirconia ceramic material with a diameter of 0.2 mm, the grinding speed is 10-20 r / min, and the grinding is carried out under a nitrogen atmosphere.
[0046] Furthermore, in some embodiments, during the preparation of the dispersed material, the inorganic carbon source includes at least one of graphene, carbon nanotubes, carbon nanofibers, and conductive carbon black.
[0047] In this application, by selecting an inorganic carbon source for coating, the conductivity is improved. Furthermore, inorganic carbon sources are less likely to react with waste gases such as water vapor generated after the oxidation-reduction of sodium metavanadate, sodium dihydrogen phosphate, and phosphorous acid at the first calcination temperature, resulting in a higher carbon content in the coating. This significantly improves the material's conductivity and reduces the powder's internal resistance. Simultaneously, inorganic carbon sources are widely available and easily accessible, which is beneficial for large-scale industrial production. If an organic carbon source is selected for coating, the material's conductivity will decrease, thereby reducing its electrochemical performance.
[0048] Furthermore, in some embodiments, before the dispersed material is calcined in stages, the dispersed material is further subjected to demagnetization treatment, and the content of magnetic foreign matter in the dispersed material after demagnetization treatment is <1ppm.
[0049] In this application, by controlling the content of magnetic foreign matter in the dispersed material to be <1ppm, the purity of the prepared composite sodium vanadium phosphate material can be increased, thus avoiding a significant reduction in the electrochemical performance of the composite sodium vanadium phosphate material due to excessively high content of magnetic foreign matter impurities.
[0050] Specifically, conventional demagnetization methods from existing technologies can be selected based on actual usage needs, as long as they can remove magnetic foreign matter from the dispersed material. For example, an electromagnetic separator can be used to achieve demagnetization.
[0051] Furthermore, in some embodiments, the first calcination includes a first heating section and a first holding section. The heating rate of the first heating section is 0.2℃ / min-0.5℃ / min, the temperature of the first holding section is 120-200℃, preferably 120-170℃, more preferably 150-170℃, and the time is 1h-2h. The second calcination includes a second heating section and a second holding section. The heating rate of the second heating section is 4℃ / min-6℃ / min, the temperature of the second holding section is 600℃-650℃, and the time is 3h-4h.
[0052] In this application, by controlling the heating rate of the first heating stage to 0.2℃ / min-0.5℃ / min, sufficient contact between the particles in the dispersed material is ensured, which is beneficial for subsequent full reaction. If the heating rate of the first heating stage is too low, the preparation efficiency will be reduced; if the heating rate of the first heating stage is too high, the particle contact time will be short, which is not conducive to subsequent full reaction. Furthermore, by controlling the temperature of the first holding stage to 120-200℃ and the time to 1h-2h, the phosphorous acid, sodium metavanadate, and sodium dihydrogen phosphate in the dispersed material undergo redox reactions at a lower temperature, avoiding the generation of impurities. If the temperature of the first holding stage is too low or too high, impurities will be generated. Furthermore, by controlling the heating rate of the second heating stage to 4℃ / min-6℃ / min, the temperature of the second calcination can be reached quickly, improving the preparation efficiency. If the heating rate of the second heating stage is too low, the preparation efficiency will be reduced; if the heating rate of the second heating stage is too high, it will affect the electrochemical performance of the material. Furthermore, by controlling the temperature of the second heat preservation section to 600℃-650℃ and the time to 3h-4h, on the one hand, calcination at a higher temperature makes the particles more compact and the compaction density higher, and the inorganic carbon source can fully coat the sodium vanadium phosphate to form a carbon coating layer, effectively improving the conductivity of the composite sodium vanadium phosphate material and reducing the internal resistance of the powder, thereby significantly improving the electrochemical performance of the composite sodium vanadium phosphate material; if the temperature of the second heat preservation section is too low or too high, the compaction density of the material will be reduced, thereby reducing the electrochemical performance of the composite sodium vanadium phosphate material.
[0053] Specifically, the heating rate of the first heating stage can be 0.2℃ / min, 0.3℃ / min, 0.4℃ / min, 0.5℃ / min, or any value within this range; the temperature of the first holding stage can be 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, or any value within this range; the holding time of the first holding stage can be 1h, 1.5h, 2h, or any value within this range; the heating rate of the second heating stage can be 4℃ / min, 4.5℃ / min, 5℃ / min, 5.5℃ / min, 6℃ / min, or any value within this range; the temperature of the second holding stage can be 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, or any value within this range; the holding time of the second holding stage can be 3h, 3.5h, 4h, or any value within this range.
[0054] Understandably, calcination can be carried out in a roller furnace, which can be divided into a first heating zone, a first holding zone, a second heating zone, a second holding zone, and a cooling zone, in which the dispersed material is calcined and cooled.
[0055] Furthermore, in some embodiments, after the dispersed material is calcined in stages, a cooling treatment is also included, and the volume ratio of the inert gas introduced in the first heating stage, the first heat preservation stage, the second heating stage, and the second heat preservation stage is (6-10):(4-6):(2-4):1; and / or, the inert gas includes at least one of nitrogen and argon.
[0056] In this application, by controlling the volume ratio of the inert gas introduced in the first heating stage, the first holding stage, the second heating stage, and the second holding stage to (6-10):(4-6):(2-4):1, the reaction can proceed fully and the electrochemical performance of the composite sodium vanadium phosphate material can be improved. However, if the volume ratio of the inert gas introduced in the first heating stage, the first holding stage, the second heating stage, and the second holding stage is too low or too high, side reactions will occur in the material, reducing the electrochemical performance of the composite sodium vanadium phosphate material.
[0057] In addition, the volume ratio of the inert gas introduced during the cooling process to the inert gas introduced in the second insulation section is (2-4):1.
[0058] Furthermore, in some embodiments, the humidity of the calcining furnace in the first insulation section is ≤2.0%, and the furnace pressure is 30Pa-60Pa; and / or, the furnace pressure in the second insulation section is 30Pa-50Pa; the cooling process specifically includes: a cooling rate of 100-200℃ / h, and cooling down to the temperature of the material ≤100℃.
[0059] In this application, by controlling the humidity of the calcining furnace in the first insulation section to be ≤2.0% and the furnace pressure to be 30Pa-60Pa, water vapor generated by the oxidation-reduction reaction can be prevented from entering the second insulation section and reacting with the inorganic carbon source, reducing the content of coated carbon, and thus reducing the electrochemical performance of the composite sodium vanadium phosphate material. By controlling the furnace pressure in the second insulation section to be 30Pa-50Pa, it is easier for the inorganic carbon source to fully coat the material surface and form a carbon coating layer. By controlling the cooling rate to be 100-200℃ / h and cooling down to the temperature of the material ≤100℃, the crystals can grow uniformly, improving the structural stability of the composite sodium vanadium phosphate material, and thus improving the electrochemical performance of the composite sodium vanadium phosphate material.
[0060] Secondly, embodiments of this application provide a composite sodium vanadium phosphate material, prepared by any of the above-mentioned preparation methods, wherein the compaction density of the composite sodium vanadium phosphate material is 2.2 g / mL-2.4 g / mL, and the specific surface area of the composite sodium vanadium phosphate material is 8 m². 2 / g-10m 2 / g, the D50 particle size of the composite sodium vanadium phosphate material is 1μm-3μm.
[0061] In this application, the prepared composite sodium vanadium phosphate material has a high compaction density.
[0062] Thirdly, embodiments of this application provide a positive electrode sheet comprising the aforementioned composite sodium vanadium phosphate material.
[0063] In the technical solution of this application embodiment, the positive electrode sheet contains the above-mentioned composite sodium vanadium phosphate material, thus having better rate performance and electrochemical performance.
[0064] In a fourth aspect, embodiments of this application provide a secondary battery, including the aforementioned positive electrode sheet.
[0065] In the technical solution of this application embodiment, the secondary battery includes the above-mentioned positive electrode sheet, and thus has better rate performance and electrochemical performance.
[0066] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0067] The performance test data of the industrial-grade sodium metavanadate used in this application are shown in Table 1 below: Table 1 Performance test data of industrial grade sodium metavanadate
[0068] The performance test data of the industrial-grade anhydrous sodium dihydrogen phosphate used are shown in Table 2 below: Table 2 Performance test data of industrial grade anhydrous sodium dihydrogen phosphate
[0069] The performance test data of the phosphorous acid used are shown in Table 3 below: Table 3 Performance test data of phosphorous acid
[0070] The performance test data of the graphene used are shown in Table 4 below: Table 4 Performance test data of graphene
[0071] Among them, the elements were tested by ICP, the particle size was tested by laser particle size analyzer, C was tested by carbon-sulfur analyzer, BET was tested by nitrogen adsorption method, chloride ions and sulfate ions were tested by ion chromatography, water-insoluble matter was tested by gravimetric method, pH was tested by pH meter, and magnetic foreign matter was tested by magnetic adsorption-gravimetric method.
[0072] I. Preparation Method Example 1 A method for preparing a composite sodium vanadium phosphate material includes the following steps: S1. Industrial-grade sodium metavanadate, industrial-grade anhydrous sodium dihydrogen phosphate, phosphorous acid, and graphene powder are mixed in a molar ratio of 2:1.03:2:1.5 and then placed in a planetary ball mill for ball milling. The inner wall of the planetary ball mill is made of ceramic material (zirconia ceramic with a yttrium content of 4%), and the grinding balls are made of zirconia ceramic material with a diameter of 0.2 mm. The grinding speed is 15 r / min, and the material is ground until the D100 particle size is 0.93 μm. During the grinding process, nitrogen gas is first introduced into the grinding tank to replace the air. The ground material is then sieved through a 150-mesh ultrasonic vibrating screen. After measuring the magnetic foreign matter content of the undersize material to be 1.8 ppm, an electromagnetic separator is used to demagnetize the undersize material until the magnetic foreign matter content is 0.9 ppm, thus obtaining a dispersed material. S2. The dispersed material obtained in step S1 is placed in a roller furnace for segmented calcination. The roller furnace sequentially includes a first heating section, a first holding section, a second heating section, a second holding section, and a cooling section. The heating rate of the first heating section is controlled at 0.4℃ / min, raising the temperature to the temperature of the first holding section (180℃). Calcination is carried out at the first holding section temperature for 1.5 hours. Then, the heating rate of the second heating section is controlled at 5℃ / min, raising the temperature to the temperature of the second holding section (630℃). Calcination is carried out at the second holding section temperature for 3.5 hours. Then... The cooling rate is 150℃ / h, and the material is discharged after the temperature is ≤100℃. During the calcination process, the volume of nitrogen introduced per hour is 1.5 times the volume of the roller furnace. The induced draft fan is controlled to keep the humidity in the first heat preservation calcination section ≤2.0%. The volume ratio of nitrogen introduced per hour in the first heating section, the first heat preservation section, the second heating section, the second heat preservation section and the cooling section is 4:2.5:1.5:0.5:1.5. The furnace pressure in the first heat preservation section is maintained at 45Pa and the furnace pressure in the second heat preservation section is maintained at 40Pa. S3. After exiting the furnace, the product is pulverized by airflow to a particle size of 2.1μm, then screened to remove iron and vacuum packaged to obtain composite sodium vanadium phosphate material. Iron removal is carried out by a combination of an electromagnetic iron separator and a permanent magnet iron separator. Vacuum packaging is carried out in a constant temperature and humidity room with a humidity of 5-10% and a temperature of 25±5℃.
[0073] Example 2 A method for preparing a composite sodium vanadium phosphate material includes the following steps: S1. Industrial-grade sodium metavanadate, industrial-grade anhydrous sodium dihydrogen phosphate, phosphorous acid, and graphene powder are mixed in a molar ratio of 2:1.02:2:2 and then placed in a planetary ball mill for ball milling. The inner wall of the planetary ball mill is made of ceramic material (zirconia ceramic with a yttrium content of 4%), and the grinding balls are made of zirconia ceramic material with a diameter of 0.2 mm. The grinding speed is 15 r / min, and the material is ground until the D100 particle size is 0.93 μm. During the grinding process, nitrogen gas is first introduced into the grinding jar to replace the air. The ground material is then sieved through a 150-mesh ultrasonic vibrating screen. After measuring the magnetic foreign matter content of the undersize material to be 2.0 ppm, an electromagnetic separator is used to demagnetize the undersize material until the magnetic foreign matter content is 0.8 ppm, thus obtaining a dispersed material. S2. The dispersed material obtained in step S1 is placed in a roller furnace for segmented calcination. The roller furnace sequentially includes a first heating section, a first holding section, a second heating section, a second holding section, and a cooling section. The heating rate of the first heating section is controlled at 0.2℃ / min, and the temperature is raised to the temperature of the first holding section (200℃). The material is then held at the first holding section temperature for 1 hour. The heating rate of the second heating section is then controlled at 6℃ / min, and the temperature is raised to the temperature of the second holding section (600℃). The material is held at the second holding section temperature for 4 hours, and then the material is cooled down. The material is cooled at a rate of 100℃ / h until its temperature is ≤100℃ before being discharged. During the calcination process, the volume of nitrogen introduced per hour is 1.5 times the volume of the roller furnace. The induced draft fan is controlled to keep the humidity in the first insulation section ≤2.0%. The volume ratio of nitrogen introduced per hour in the first heating section, the first insulation section, the second heating section, the second insulation section, and the cooling section is 4:2.5:1.5:0.5:1.5. The furnace pressure in the first insulation section is maintained at 30Pa, and the furnace pressure in the second insulation section is maintained at 40Pa. S3. After exiting the furnace, the product is pulverized by airflow to a particle size of 1.5μm, then screened to remove iron and vacuum packaged to obtain composite sodium vanadium phosphate material. Iron removal is carried out by a series connection of an electromagnetic iron separator and a permanent magnet iron separator. Vacuum packaging is carried out in a constant temperature and humidity room with a humidity of 5-10% and a temperature of 25±5℃.
[0074] Example 3 A method for preparing a composite sodium vanadium phosphate material includes the following steps: S1. Industrial-grade sodium metavanadate, industrial-grade anhydrous sodium dihydrogen phosphate, phosphorous acid, and graphene powder are mixed in a molar ratio of 2:1.04:2:1 and then placed in a planetary ball mill for ball milling. The inner wall of the planetary ball mill is made of ceramic material (zirconia ceramic with a yttrium content of 4%), and the grinding balls are made of zirconia ceramic material with a diameter of 0.2 mm. The grinding speed is 15 r / min, and the material is ground until the D100 particle size is 0.93 μm. During the grinding process, nitrogen gas is first introduced into the grinding jar to replace the air. The ground material is then sieved through a 150-mesh ultrasonic vibrating screen. After measuring the magnetic foreign matter content of the undersize material to be 2.5 ppm, an electromagnetic separator is used to demagnetize the undersize material until the magnetic foreign matter content is 1.0 ppm, thus obtaining a dispersed material. S2. The dispersed material obtained in step S1 is placed in a roller furnace for segmented calcination. The roller furnace sequentially includes a first heating section, a first holding section, a second heating section, a second holding section, and a cooling section. The heating rate of the first heating section is controlled at 0.5℃ / min, raising the temperature to the temperature of the first holding section (120℃). Calcination is carried out at the first holding section temperature for 2 hours. Then, the heating rate of the second heating section is controlled at 4℃ / min, raising the temperature to the temperature of the second holding section (650℃). Calcination is carried out at the second holding section temperature for 3 hours, and then the material is cooled down. The material is cooled at a rate of 200℃ / h until its temperature is ≤100℃ before being discharged. During the calcination process, the volume of nitrogen introduced per hour is 1.5 times the volume of the roller furnace. The induced draft fan is controlled to keep the humidity in the first insulation section ≤2.0%. The volume ratio of nitrogen introduced per hour in the first heating section, the first insulation section, the second heating section, the second insulation section, and the cooling section is 4:2.5:1.5:0.5:1.5. The furnace pressure in the first insulation section is maintained at 60Pa, and the furnace pressure in the second insulation section is maintained at 40Pa. S3. After exiting the furnace, the product is pulverized by airflow to a particle size of 2.5μm, then screened to remove iron and vacuum packaged to obtain composite sodium vanadium phosphate material. Iron removal is carried out by a series connection of an electromagnetic iron separator and a permanent magnet iron separator. Vacuum packaging is carried out in a constant temperature and humidity room with a humidity of 5-10% and a temperature of 25±5℃.
[0075] Example 4 A method for preparing a composite sodium vanadium phosphate material includes the following steps: S1. Industrial-grade sodium metavanadate, industrial-grade anhydrous sodium dihydrogen phosphate, phosphorous acid, and graphene powder are mixed in a molar ratio of 2:1.05:2:1.8 and then placed in a planetary ball mill for ball milling. The inner wall of the planetary ball mill is made of ceramic material (zirconia ceramic with a yttrium content of 4%), and the grinding balls are made of zirconia ceramic material with a diameter of 0.2 mm. The grinding speed is 15 r / min, and the material is ground until the D100 particle size is 0.93 μm. During the grinding process, nitrogen gas is first introduced into the grinding tank to replace the air. The ground material is then sieved through a 150-mesh ultrasonic vibrating screen. After measuring the magnetic foreign matter content of the undersize material to be 1.5 ppm, an electromagnetic separator is used to demagnetize the undersize material until the magnetic foreign matter content is 0.6 ppm, thus obtaining a dispersed material. S2. The dispersed material obtained in step S1 is placed in a roller furnace for segmented calcination. The roller furnace sequentially includes a first heating section, a first holding section, a second heating section, a second holding section, and a cooling section. The heating rate of the first heating section is controlled at 0.3℃ / min, raising the temperature to the temperature of the first holding section (150℃). Calcination is carried out at the first holding section temperature for 2 hours. Then, the heating rate of the second heating section is controlled at 5℃ / min, raising the temperature to the temperature of the second holding section (630℃). Calcination is carried out at the second holding section temperature for 3.5 hours. Then... The cooling rate is 180℃ / h, and the material is discharged after the temperature is ≤100℃. During the calcination process, the volume of nitrogen introduced per hour is 1.5 times the volume of the roller furnace. The induced draft fan is controlled to keep the humidity in the first heat preservation section ≤2.0%. The volume ratio of nitrogen introduced per hour in the first heating section, the first heat preservation section, the second heating section, the second heat preservation section and the cooling section is 4:2.5:1.5:0.5:1.5. The furnace pressure in the first heat preservation section is maintained at 40Pa, and the furnace pressure in the second heat preservation section is maintained at 40Pa. S3. After exiting the furnace, the product is pulverized by airflow to a particle size of 1.8μm, then screened to remove iron and vacuum packaged to obtain composite sodium vanadium phosphate material. Iron removal is carried out by a combination of an electromagnetic iron separator and a permanent magnet iron separator. Vacuum packaging is carried out in a constant temperature and humidity room with a humidity of 5-10% and a temperature of 25±5℃.
[0076] Example 5 The preparation method of the composite sodium vanadium phosphate material in this embodiment is basically the same as that in Example 1, except that graphene is replaced with carbon nanotubes.
[0077] Example 6 The preparation method of the composite sodium vanadium phosphate material in this embodiment is basically the same as that in Example 1, except that graphene is replaced with carbon nanofibers.
[0078] Example 7 The preparation method of the composite sodium vanadium phosphate material in this embodiment is basically the same as that in Example 1, except that graphene is replaced with conductive carbon black.
[0079] Comparative Example 1 Vanadium pentoxide, sodium dihydrogen phosphate, and glucose were mixed, with the molar ratio of sodium, vanadium, and phosphorus being the same as in Example 1. Water was added to form a slurry with a solid content of 35%. The slurry was then ground until the D100 particle size was 0.93 μm. Grinding was stopped, and the mixture was spray-dried and calcined to obtain a composite sodium vanadium phosphate material. The calcination process is the same as in Example 1.
[0080] Comparative Example 2 The preparation method of the composite sodium vanadium phosphate material in this comparative example is basically the same as that in Example 1, except that graphene is replaced with glucose.
[0081] Comparative Example 3 The preparation method of the composite sodium vanadium phosphate material in this comparative example is basically the same as that in Example 1. The difference is that the dispersed material is directly subjected to a second heating calcination and a second heat preservation calcination.
[0082] Comparative Example 4 The preparation method of the composite sodium vanadium phosphate material in this comparative example is basically the same as that in Example 1, except that the temperature of the first heat preservation section is 100℃.
[0083] Comparative Example 5 The preparation method of the composite sodium vanadium phosphate material in this comparative example is basically the same as that in Example 1, except that the temperature of the first heat preservation section is 220℃.
[0084] Comparative Example 6 The preparation method of the composite sodium vanadium phosphate material in this comparative example is basically the same as that in Example 1, except that the heating rate of the second heating calcination is 80℃ / min.
[0085] Comparative Example 7 The preparation method of the composite sodium vanadium phosphate material in this comparative example is basically the same as that in Example 1, except that the heating rate of the second heating calcination is 220℃ / min.
[0086] II. Testing Methods 1. SEM testing The composite sodium vanadium phosphate materials prepared in Example 1 and Comparative Example 1 were subjected to SEM testing, and the results are as follows: Figure 1 and 2 As shown.
[0087] 2. XRD test The composite sodium vanadium phosphate material prepared in Example 1 was subjected to XRD testing, and the results are as follows: Figure 3 As shown.
[0088] 3. Performance testing of composite sodium vanadium phosphate materials The properties of the composite sodium vanadium phosphate materials prepared in Examples 1-7 and Comparative Examples 1-7 were tested, and the results are shown in Tables 5-7 below.
[0089] Among them, the contents of Na, V, P, free sodium, K, Ni, Cr, Cu, Zn, Ca, Mg, Al, and Fe were measured by ICP; the contents of C were tested by a carbon-sulfur analyzer; the contents of BET were tested by nitrogen adsorption; the internal resistance of powder was measured by the four-probe method at a test pressure of 8 MPa; D10, D50, and D90 were tested by a laser particle size analyzer; pH was measured by adding 90 g of pure water to 10 g of material, stirring for 10 min, and then measuring with a pH meter; the contents of magnetic foreign matter were measured by magnetic particle adsorption; the compaction density was measured by a compaction density analyzer at a test pressure of 3 T; and the moisture content was measured by a KF moisture analyzer at a test temperature of 170℃.
[0090] 3. Performance testing of secondary batteries The composite sodium vanadium phosphate materials prepared in Examples 1-7 and Comparative Examples 1-7 were mixed with polyvinylidene fluoride (PVDF) and conductive carbon black (SP) in a mass ratio of 85:7:8 and then homogenized into a slurry. The slurry was then coated onto aluminum foil to prepare a button cell. The electrolyte was a 1 mol / L lithium hexafluorophosphate solution. The charge-discharge curves were measured at 1C, 5C, 10C and 20C rates, with a voltage range of 2.0-4.0V. The results are shown in Table 8 below.
[0091] III. Analysis of Test Results for Each Embodiment and Comparative Example from Figure 1 and 2 As can be seen from the above, the composite sodium vanadium phosphate material prepared in this application is granular and has no pores, and has a high degree of density; while the composite sodium vanadium phosphate material prepared in Comparative Example 1 is loose and porous, with a large number of pores and voids. Therefore, the composite sodium vanadium phosphate material in this application has a high compaction density.
[0092] from Figure 3 As can be seen from the data, the composite sodium vanadium phosphate material prepared in this application has no obvious impurity peaks and has high purity.
[0093] Furthermore, the relevant performance test results of the composite sodium vanadium phosphate materials prepared in the examples and comparative examples are shown in Tables 5-7 below.
[0094] Table 5 Performance test data of the composite sodium vanadium phosphate material prepared in Example 1
[0095] Table 6 Performance test data of the composite sodium vanadium phosphate material prepared in Comparative Example 1
[0096] Table 7 Performance test data of the composite sodium vanadium phosphate materials prepared in the examples and comparative examples
[0097] As shown in Table 7, the composite sodium vanadium phosphate materials prepared in Examples 1-7 exhibit lower powder internal resistance and higher compaction density. In Examples 5-7, graphene was replaced with carbon nanotubes, carbon nanofibers, and conductive carbon black, respectively. The results indicate that the powder internal resistance of the prepared composite sodium vanadium phosphate materials increased to some extent. This is because graphene, being a two-dimensional sheet structure, provides a larger contact area (surface contact) with the sodium vanadium phosphate material after coating, enabling the formation of a better electronic conduction network. Conversely, the contact area between carbon nanotubes, carbon nanofibers, and conductive carbon black and the sodium vanadium phosphate material is reduced after coating. Therefore, compared to other inorganic carbon sources, the composite sodium vanadium phosphate material using graphene for carbon coating exhibits lower powder internal resistance.
[0098] In Comparative Example 1, the powder internal resistance of the composite sodium vanadium phosphate material prepared using conventional methods with vanadium pentoxide, sodium dihydrogen phosphate, and glucose was significantly increased, while the compaction density was significantly decreased, resulting in a noticeable decline in material performance. In Comparative Example 2, using an organic carbon source, the powder internal resistance of the prepared composite sodium vanadium phosphate material increased to some extent, while the compaction density decreased to some extent, leading to a certain degree of decline in material performance. In Comparative Example 3, directly undergoing a second heating and second holding calcination resulted in a certain degree of increase in the powder internal resistance and a certain degree of decrease in the compaction density of the prepared composite sodium vanadium phosphate material, leading to a certain degree of decline in material performance. In Comparative Examples 4 and 5, where the first calcination temperature was either too low or too high, the powder internal resistance of the prepared composite sodium vanadium phosphate material increased to some extent, and the content of magnetic foreign matter increased to some extent, indicating incomplete reaction and the generation of impurities, which led to a certain degree of decline in material performance. In Comparative Examples 6 and 7, the heating rate of the second heating calcination was relatively high, which led to a certain increase in the powder internal resistance and the content of magnetic foreign matter in the prepared composite sodium vanadium phosphate material. Furthermore, the faster the heating rate, the higher the content of magnetic foreign matter, indicating that the heating rate of the second heating calcination was too fast, resulting in incomplete reaction and the generation of impurities, which led to a certain degree of decline in the material performance.
[0099] Table 8 Performance test data of secondary batteries
[0100] As shown in Table 8, the secondary batteries prepared using the composite sodium vanadium phosphate materials obtained in Examples 1-7 exhibit higher charge-discharge capacities at 1C, 5C, 10C, and 20C rates. In Examples 5-7, the powder internal resistance of the prepared composite sodium vanadium phosphate materials increased to some extent due to the replacement of graphene with carbon nanotubes, carbon nanofibers, and conductive carbon black, respectively. Therefore, when using the composite sodium vanadium phosphate materials prepared in Examples 1 and 5-7 to prepare secondary batteries, the charge-discharge capacities of the secondary batteries prepared using the cathode materials of Examples 5-7 are somewhat lower than those prepared using the cathode materials of Example 1 at 1C, 5C, 10C, and 20C rates.
[0101] Furthermore, the secondary battery prepared using the cathode material in Comparative Example 1 showed a significant decrease in charge-discharge capacity at 10C and 20C rates, indicating a marked decline in the electrochemical performance of the cathode material. In Comparative Example 2, the use of an organic carbon source in the cathode material preparation process resulted in a decrease in discharge efficiency at 1C, 5C, 10C, and 20C rates, indicating a significant decline in the electrochemical performance of the cathode material. In Comparative Example 3, the direct second heating and second holding calcination during cathode material preparation resulted in a decrease in discharge efficiency at 1C, 5C, and 10C rates, indicating a significant decline in the electrochemical performance of the cathode material. In Comparative Examples 4 and 5, increasing or decreasing the first calcination temperature resulted in a decrease in discharge efficiency at 1C, 5C, and 10C rates, indicating incomplete reaction and impurity generation, leading to a decline in the electrochemical performance of the cathode material. In Comparative Examples 6 and 7, increasing the heating rate of the second heating process during the preparation of the cathode material resulted in a certain degree of decrease in the discharge efficiency of the secondary batteries under 1C, 5C, and 10C rate conditions. Furthermore, the faster the heating rate, the lower the 1C discharge capacity and discharge efficiency, the 5C charge-discharge capacity, and the 10C charge-discharge capacity and discharge efficiency. The results indicate that an excessively fast heating rate in the second heating process leads to incomplete reactions, easily generating impurities, and causing a certain degree of decrease in the electrochemical performance of the cathode material.
[0102] In summary, the raw materials used in this application exhibit low ignition loss and produce no waste gases such as ammonia or carbon dioxide, only a small amount of water vapor, demonstrating good environmental performance and belonging to a low-carbon emission process. Furthermore, this application employs a dry mixing process, which, compared to traditional wet mixing processes, avoids drying the raw materials, thereby shortening the process and reducing costs. In addition, this application utilizes a redox reaction to achieve the valence state transformation of vanadium and phosphorus, and through the oxidation reaction, achieves better fusion of the phosphorus and vanadium sources, providing conditions for subsequent solid-state sintering. Specifically, the process of this application includes a first calcination and a second calcination. The heating rate in the first holding section of the first calcination is slow. When the oxidation reaction occurs in the first holding section, the solids can fully contact and fuse, achieving redox at a lower temperature. This allows water vapor to be generated and extracted at a lower temperature, avoiding the consumption of carbon and fluctuations in carbon content in the high-temperature section. Consequently, the prepared composite sodium vanadium phosphate material has high compaction density and low powder internal resistance, which is beneficial for its application in secondary batteries.
[0103] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A method for preparing a composite sodium vanadium phosphate material, characterized in that, The method comprises the following steps: mixing sodium metavanadate, sodium dihydrogen phosphate, phosphorous acid and an inorganic carbon source, and then performing dispersion treatment to obtain a dispersion material; performing staged calcination on the dispersion material in an inert atmosphere to obtain a composite sodium vanadium phosphate material; wherein the staged calcination comprises first calcination and second calcination in sequence, the first calcination is performed at a calcination temperature of 120-200 DEG C, and the second calcination is performed at a calcination temperature of 600-650 DEG C.
2. The method for preparing the composite sodium vanadium phosphate material according to claim 1, characterized in that, In the preparation of the dispersion material, the molar ratio of sodium metavanadate, sodium dihydrogen phosphate, phosphorous acid and the inorganic carbon source is 2:(1.02-1.05):2:(1-2); and / or the dispersion treatment comprises ball milling dispersion treatment, and the D100 particle size of the dispersion material is ≤1 μm.
3. The method for preparing the composite sodium vanadium phosphate material according to claim 1, characterized in that, In the preparation of the dispersion material, the inorganic carbon source comprises at least one of graphene, carbon nanotube, carbon nanofiber and conductive carbon black.
4. The method for preparing the composite sodium vanadium phosphate material according to claim 1, characterized in that, Before the staged calcination of the dispersion material, the dispersion material is further subjected to a demagnetization treatment, and the content of magnetic foreign matters in the dispersion material after the demagnetization treatment is <1 ppm.
5. The method for preparing the composite sodium vanadium phosphate material according to claim 1, characterized in that, The first calcination comprises a first temperature rising section and a first holding section, the temperature rising rate of the first temperature rising section is 0.2-0.5 DEG C / min, the temperature of the first holding section is 120-200 DEG C, and the time is 1-2 h; The second calcination comprises a second temperature rising section and a second holding section, the temperature rising rate of the second temperature rising section is 4-6 DEG C / min, the temperature of the second holding section is 600-650 DEG C, and the time is 3-4 h.
6. The method for preparing the composite sodium vanadium phosphate material according to claim 5, characterized in that, In the staged calcination, the volume ratio of the inert gas introduced into the first temperature rising section, the first holding section, the second temperature rising section and the second holding section is (6-10):(4-6):(2-4):1; and / or The inert gas comprises at least one of nitrogen and argon.
7. The method for preparing the composite sodium vanadium phosphate material according to claim 6, characterized in that, The humidity in the first holding section is ≤2.0%, and the furnace pressure is 30-60 Pa; and / or The furnace pressure in the second holding section is 30-50 Pa.
8. A composite sodium vanadium phosphate material, characterized in that, The composite sodium vanadium phosphate material prepared by the preparation method in any one of claims 1-7 has a compacted density of 2.2 g / mL-2.4 g / mL, a specific surface area of 8 m 2 / g-10 m 2 / g, and a D50 particle size of 1 μm-3 μm.
9. A positive electrode sheet characterized by comprising: The composite sodium vanadium phosphate material of claim 8.
10. A secondary battery characterized by comprising: The positive electrode tab of claim 9.